PERFORMANCE BASED ASSESSMENT ON YOUNG LEARNERS' SPEAKING SKILL - Tegamuni, Suhaimi (2012)
This thesis is an experimental and descriptive study which explores the use of performance based assessment to young learners' speaking achievement and teacher's perception towards the implemented assessment type to students' success in learning speaking. The study examines the effect of performance based assessment on young learners' speaking skill achievement and describes how the teacher's perception as the typical assessment being implemented. For its framework for analysis, the study draws some important theory of performance based assessment (its importance, the dealing criteria to speaking skills and young learners' characteristics), speaking ability to young learners (some practical considerations in assessing young learners), and the last is dealing with teacher's perception theory which portraits the concept of the sensory nature of stimulus, personal feelings, attitudes, drives, goals and previous related sensory experience. It is argued that performance based assessment emulate real-life contexts or conditions in which specific knowledge or skills are actually applied and performance assessment is needed for today's evaluation system. The study employed both quantitative and qualitative method. The data obtained through the use of experiment design (pretest and posttest) then questionnaire as others research methodology to obtain the descriptive data from teacher's perception. The result of the study shows that performance based assessment effects students' speaking ability and teacher's perception to students after being treated using performance based assessment is good. Students mostly show their speaking achievement at satisfactory level. In the concluding chapter, it was noted that this research also has shortcomings, that the study was conducted in a small scale so that the most likely effect is still small. Researcher sincerely hope there is further research to be conducted in a larger scale.